Web-GIS mapping for watershed and land cover area in Bengkulu - Ernawati Ernawati; Vatresia Arie; Breygas Andara; Rendra Regen (Sustinere: Journal of Environment and Sustainability, 2019)
Naturally, watershed has a function to accomodate and store water from rainfall to the lake or to the sea. It is affected by land activities and shaped as a boundary of topographic land and as a separator from the sea. Managing the area is one of essential steps for further environment assessement, i.e. decreasing water quality and vulnerability to landslides or floods. However, the ability of web-GIS technology to help the management of watershed area in Bengkulu is still unknown. Here, we showed how the process of Web GIS development for managing the watershade in Bengkulu could be achived. This study mapped the 2018 land cover area of Rindu Hati Sub-watershed by utilizing Landsat 8 satellite images using the Maximum Likelihood method. The land cover map was then processed and displayed using webGIS media. The results showed that the system accuracy for ground truth land use model result was 77.4% which could be accepted as a good result. Further assessment of pixel validation could be one of the future research. We anticipated that the results could be a starting point for more sophisticated area cover of Sumatra and Indonesia. Furthermore, this could be a major development on knowledge discovery in environment and ecology.